2024
DOI: 10.1111/jdv.19810
|View full text |Cite
|
Sign up to set email alerts
|

Deroofing: A safe, effective and well‐tolerated procedure in patients with hidradenitis suppurativa

P. K. Krajewski,
V. Sanz‐Motilva,
S. Flores Martinez
et al.

Abstract: IntroductionHidradenitis suppurativa (HS) is a recurrent, debilitating, chronic disorder of the pilosebaceous unit. Although advances in HS treatment have been made, more than 45% of patients remain dissatisfied with systemic treatment, and more than one‐third are dissatisfied with surgical procedures.ObjectivesA prospective, observational study on the deroofing procedures in HS with special attention paid to patient satisfaction and complications.MethodsHS lesions were assessed clinically and by the use of ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The long-term outcomes and recurrence rates of minimally invasive dermatosurgical procedures exhibit variability contingent upon the specific procedure and treated condition. For instance, a study investigating wide surgical excisions for hidradenitis suppurativa reported a minimal recurrence rate of 2.5% [56].…”
Section: Long-term Results and Recurrence Ratesmentioning
confidence: 99%
“…The long-term outcomes and recurrence rates of minimally invasive dermatosurgical procedures exhibit variability contingent upon the specific procedure and treated condition. For instance, a study investigating wide surgical excisions for hidradenitis suppurativa reported a minimal recurrence rate of 2.5% [56].…”
Section: Long-term Results and Recurrence Ratesmentioning
confidence: 99%